Perinatal aspects of preservation of pregnancy with chronic stress - І. А. Жабченко; С. В. Тертична-Телюк; Н. Г. Корнієць; Т. М. Коваленко (Publishing House TRILIST, 2019)
Aim of the study is to identify the peculiar issues associated with psycho-emotional state and the related stress-associated hormones and micronutrients in pregnant-displace individuals for further improvement of programmes for antenatal research. Dynamic prospective clinical-paraclinical examination of 96 pregnant women (experimental group) - temporary displaced individuals with gestation period of more than 22 weeks who have been treated and gave birth to their children in the Central Municipal Hospital in Rubizhne and Perinatal Centre in Severodonetsk, Lugansk region was performed. The control group consists of 39 randomly selected pregnant women for the purposes of prospective research that are living in the areas under the control of Ukraine government. All pregnant women were examined; the evaluation of psycho-emotional state of examined pregnant was conducted with the help of screening by performing clinical interviews together with routine questioning. The questionnaires that contained the questions of Spielberg's tests in the Khanin modification were used. Concentration of stress-associated hormones in the blood serum, calcium and magnesium was identified using the method of solid-phase immunoferment analysis and the colorimetric method. According to the Spielberg's test, the average score of reactive anxiety in the experimental group exceeded the analogous indicator in the control group by 1.6 times. The indicators of personal anxiety exceeded the normal indicator in the control group by 2.2 times. Cortisol concentration in the blood serum in experimental group exceeded the upper physiological standard by 5.5% and exceeded the analogous indicator in the control group by 43.4%. The increase prolactin value was yet observed in the II trimester by 13.3% compared to the upper level of physiological standard; by 20.3% compared to the average indicator of this hormone in the control group. In the III trimester its concentration in both groups was within normal ranges, but in the experimental group it was higher by 10.5%. Calcium in the blood serum in the experimental group was higher by 19.2% in comparison to the physiological standard and by 9.6% higher if compared to the analogous indicator in the control group. At the same time, the pregnant women in the experimental group have low magnesium value. Taking into account the identified patterns, it is useful to categorise the pregnant women from among the internally displaced individuals as the group of high risk with respect to the development of obstetric and perinatal complications.